1996
DOI: 10.1016/s0741-5214(96)70022-8
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the excluded abdominal aortic aneurysm sac: Long-term follow-up of 831 patients

Abstract: Retroperitoneal exclusion and bypass is a viable alternative to traditional open endoaneurysmorraphy in surgery for abdominal aortic aneurysm. Most excluded aneurysm sacs have thrombosis without any long- or short-term complications; however, in a small number of patients delayed rupture of patent aneurysm occurs, thus emphasizing the need for diligent follow-up and appropriate intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 9 publications
(1 reference statement)
3
39
0
3
Order By: Relevance
“…The findings of Resnikoff et al (14) and our data indicate that CT is the single most sensitive method for detecting leakages. Although color Doppler ultrasonography (US) is a useful method for demonstrating leakages, its application is limited because a majority of patients with aortic leakages tend to be older and obese, and, thus, some segments of the infrarenal aorta may not be adequately depicted.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The findings of Resnikoff et al (14) and our data indicate that CT is the single most sensitive method for detecting leakages. Although color Doppler ultrasonography (US) is a useful method for demonstrating leakages, its application is limited because a majority of patients with aortic leakages tend to be older and obese, and, thus, some segments of the infrarenal aorta may not be adequately depicted.…”
Section: Discussionsupporting
confidence: 72%
“…Resnikoff et al (14) examined 831 patients who underwent nonresective treatment of infrarenal abdominal aortic aneurysms by means of proximal and distal ligation of the aneurysmal sac combined with aortic bypass grafting, and reported only 17 (2%) retrograde leakages, which were supplied by the lumbar, hypogastric, or inferior mesenteric arteries. A high percentage of these patients had ruptures during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, endoleak following conventional "inlay" open aneurysm surgery is rare with only a few reports in the world literature. The first report was by Chan et al, with a series of six cases of type I endoleak (one proximal, five distal anastomotic leaks), which presented between 6 weeks and 18 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the endovascular repair has to rely on thrombosis of these branches following thrombus form ation wit hin the aneurysm sac. The former aneurysm ligation technique demonstrated that this mechanism is likely to occur, but it did not preclude further aneurysm rupture in a few cases (7). The potential of lumbar arteries for subsequent thrombosis after occlusion of their orifices is not known.…”
Section: Discussionmentioning
confidence: 99%